Analysis of Human Resource Development in Improving Village-Owned Enterprises in Karangasem Regency, Bali - Harsana, Minta; Fauziah, Afia (Devotion : Journal of Research and Community Service, 2023)
The Human Resource (HR) crisis is one of the problems for village development, especially the establishment and development of BUMDes. The way BUMDes works is through community economic activities in the form of institutions or business entities that are managed professionally but still rely on the original potential of the village. One of the potential village businesses owned by Karangasem Regency is in the tourism sector. This study is intended to determine the potential and capacity of Karangasem BUMDes human resources in tourism development in Kab. Karangasem Bali. The methods and approaches used in the BUMDes HR Potential Analysis activity in the development of Karangasem tourism in Bali by taking into account the suitability of the actual conditions in the field so that they can become a policy recommendation. Next, a SWOT analysis was carried out. In this analysis, an analysis of the internal environment and an analysis of the external environment is carried out to determine strategies, policies and programs to increase the capacity of BUMDes human resources in the development of Karangasem tourism in Bali. The target to be achieved in this research is the availability of a BUMDes HR database as a basis for setting policies to increase the capacity of Karangasem BUMDes human resources in tourism development in Bali.